Loss of agricultural soil from 2009-2024 in Celaya, Guanajuato - Mandujano-Bueno, Andrés; Buenrostro-Rodríguez, Juan Francisco; de la O-Olán, Micaela; Montero-Tavera, Víctor (Revista Mexicana de Ciencias Agrícolas, 2025)
Urban and industrial growth, along with the abandonment of agricultural land, reduces the area to produce food, which compromises the food security of the population. Establishing the dynamics of land-use change allows actions to be applied to mitigate its negative impact. The research aimed to determine the change in land use to estimate the magnitude of the reduction in agricultural land area in the municipality of Celaya, Guanajuato. To this end, the outlines of the municipal agricultural area from 2009 were updated over high-resolution images from the Google Earth Geographic Information System of 2024; of the resulting polygons, their water use condition was determined, and based on this, the potential impact on corn and bean production was calculated. The results show that in 15 years, Celaya has lost 4 647 agricultural hectares; 41% were destined for urban use, 20% for industry, 7% for roads, and 32% remain unused. The loss of agricultural land use was confirmed by the decrease in the visible atmospherically resistant index from 0.05 to -0.02. Most of the change in land use from agricultural to urban and industrial originates from well-based irrigation, while the change to disuse originates from rainfed land. The impact on agricultural production is the loss of almost 8 000 t of beans. Nevertheless, corn has increased its area sown by nearly 4 000 ha at the expense of reductions in other crops.